2017
DOI: 10.1093/gbe/evx253
|View full text |Cite
|
Sign up to set email alerts
|

Migration-Selection Balance Drives Genetic Differentiation in Genes Associated with High-Altitude Function in the Speckled Teal (Anas flavirostris) in the Andes

Abstract: Local adaptation frequently occurs across populations as a result of migration-selection balance between divergent selective pressures and gene flow associated with life in heterogeneous landscapes. Studying the effects of selection and gene flow on the adaptation process can be achieved in systems that have recently colonized extreme environments. This study utilizes an endemic South American duck species, the speckled teal (Anas flavirostris), which has both high- and low-altitude populations. High-altitude … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(38 citation statements)
references
References 158 publications
(119 reference statements)
0
38
0
Order By: Relevance
“…AKT/phosphoinositide-3 kinase signaling in the downstream of the IIS pathway in the skeletal muscle of mice can respond to acute hypoxia 47 . At the genetic level, altitude-related selection loci in speckled teal ( Anas flavirostris ) also contain genes involved in the IIS 48 , which suggests a conserved regulatory mechanism by IIS underlying the high-altitude hypoxia adaptation. The current study further demonstrated the role of the IIS pathway in energy homeostasis regulation during hypoxia adaptation.…”
Section: Discussionmentioning
confidence: 99%
“…AKT/phosphoinositide-3 kinase signaling in the downstream of the IIS pathway in the skeletal muscle of mice can respond to acute hypoxia 47 . At the genetic level, altitude-related selection loci in speckled teal ( Anas flavirostris ) also contain genes involved in the IIS 48 , which suggests a conserved regulatory mechanism by IIS underlying the high-altitude hypoxia adaptation. The current study further demonstrated the role of the IIS pathway in energy homeostasis regulation during hypoxia adaptation.…”
Section: Discussionmentioning
confidence: 99%
“…Among these, the yellow-billed pintail and cinnamon teal are the most recent species to diverge from their low-altitude ancestor(s) and arrive at high altitude, based on mitochondrial DNA divergence (McCracken et al, 2009b;Wilson et al, 2013). The speckled teal has had the longest time at altitude since diverging from its lowaltitude ancestors (Graham et al, 2018). The ruddy duck likely lies more intermediate in evolutionary time since divergence from its low-altitude ancestors (Muñoz-Fuentes et al, 2013).…”
Section: Materials and Methods Waterfowlmentioning
confidence: 99%
“…This approach allowed four independent comparisons of the effect of adaptation to high altitude on cardiovascular O 2 transport. All of these species are derived from low-altitude waterfowl populations (Johnson and Sorenson, 1999), but exhibit differences in genetic divergence that are suggestive of varying degrees of genetic isolation and evolutionary time at high altitude (McCracken et al, 2009b;Wilson et al, 2013;Muñoz-Fuentes et al, 2013;Graham et al, 2018). We wished to determine whether the high-altitude populations would demonstrate convergent or divergent enhancements in circulatory O 2 transport during progressive hypoxia, and the extent to which their responses to hypoxia were similar to or distinct from those observed in previous studies of the high-altitude resident Andean goose and the high-altitude migrant bar-headed goose (Laguë et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, we estimate that the two torrent ducks likely diverged in the early-to mid-Pleistocene (mtDNA divergence time = 600,000 ybp, 95% HPD range = 1.2 Mya to 200,000 ybp, Figure 3d; and nuclear divergence time = 782,490 ybp). Compared to other species found in the Andes of Argentina and Peru, divergence estimates for torrent ducks are some of the oldest, although comparable to those estimated between speckled teal (Bulgarella et al, 2012;Graham et al, 2017;McCracken et al, 2009;Wilson et al, 2012). Therefore, torrent ducks can be considered an older Andean resident probably tightly associated to the formation of river systems.…”
Section: Deep Genetic Divergence Between Subspeciesmentioning
confidence: 57%
“…The reduced gene flow between the two torrent ducks subspecies is most likely due to their habitat specialization and lack of suitable intermediate habitat, particularly where the Andes show the highest mountain ranges and widest extension that harbors a complex riverine spatial structure (Capitonio et al, 2011;Gonzalez & Pfiffner, 2011). In contrast, two subspecies of speckled teal (Anas flavisrostris) with similar distribution range and divergence time show relatively less genomic divergence and asymmetric gene flow (Graham et al, 2017). Long-standing and recurrent gene flow in speckled teal might be facilitated by the lack of habitat specialization (i.e., lakes, pond, and also rivers), and a larger number of habitats present in the lowlands due to a broader flat topography than in the highlands in the Southern Andes.…”
Section: Deep Genetic Divergence Between Subspeciesmentioning
confidence: 99%